Fatigue Life and Topology Optimization of Racing Car Upright for Formula SAE Electric - Alief Wikarta; Yusuf Kaelani; Fahreza Aji Taruna; Bernardus Herdian Arveliko Indwindra; Linggar Alvinsyah Trengginas (Automotive Experiences, 2024)
This research aimed to reduce the mass of a racing car upright made from Aluminum Alloy 7075-T6 through topology optimization and fatigue life analysis. The design process included stages of meeting over-design conditions, optimizing mass reduction for the uprights, and smoothing critical areas. Finite element simulation was used throughout to analyze strength and fatigue life, considering loading conditions, geometry, and material properties. Special attention was given to critical areas to ensure optimized stress distribution and minimize stress concentration. The results showed that extreme loading conditions occur during braking while turning. The optimization process followed boundary conditions and design requirements, resulting in a 56% mass reduction from 944.39 grams to 416.43 grams while maintaining structural integrity. The optimized design featured a larger fillet radius, reducing stress concentration in critical areas and lowering the maximum stress value. The final design demonstrated a smoother structure with reduced stress concentrations, confirming the effectiveness of the optimization.